The purchasing power of money : its determination and relation to credit interest and crises - Fisher, Irving (New York : A. M. Kelley, 1963)
The purpose of this book is to set forth the principles determining the purchasing power of money and to apply those principles to the study of historical changes in that purchasing power, including in particular the recent change in the cost of living, which has aroused world-wide discussion.
includes index
Bibliographical footnotes.
usc 31/05/2017
Loans
Keywords: Purchasing power